Heat Capacity and Thermodynamic Characteristics of Sodium and Potassium Nickelite-Manganites of Neodymium of NdNa2NiMnO5 and NdK2NiMnO5 - Shuga Bulatovna Kasenova; Zhenisgul Imangalievna Sagintaeva; Bulat Kunurovich Kasenov; Erbolat Ermekovich Kuanyshbekov; Aigul Tanirbergenovna Ordabaeva; Manara Amangeldievna Isabaeva (Applied Sciences, 2025)
For the first time, neodymium nickel manganites NdNa2NiMnO5 and NdK2NiMnO5 were synthesized via the solid-state interaction method, and they crystallize in a cubic system. Using experimental dynamic calorimetry in the temperature range of 298.15–673 K, the temperature dependences of the heat capacity of NdNa2NiMnO5 and NdK2NiMnO5 were studied. At 423 K, both compounds exhibited anomalous heat capacity jumps on the C0p~f(T) dependency, likely corresponding to second-order phase transitions. Considering the phase transition temperatures, equations for the temperature dependence of heat capacity were derived, accurately describing the experimental data. Based on the experimental C0p(T) data and calculated S0 (298.15) values, temperature dependences of C0p(T) and the thermodynamic functions S0(T), H°(T)–H0(298.15), and Φxx(T) were determined for the studied compounds within the 298.15–673 K range. The analysis of electrophysical data confirmed the semiconducting and metallic nature of the conductivity, as well as identified the band gap and activation energy of conductivity. These results are valuable for the application of these materials in electronics and for controlling conductivity.